2021
DOI: 10.1177/17504589211022314
|View full text |Cite
|
Sign up to set email alerts
|

Clinical accuracy of non-contact forehead infrared thermometer and infrared tympanic thermometer in postoperative adult patients: A comparative study.

Abstract: Core temperature monitoring is important for the assessment and prevention of possible postoperative complications. The aim of the present study was to examine the agreement between the core temperature values and the forehead, tympanic membrane and axillary values in postoperative adult patients in clinical practice. The study measured the core temperature of 65 patients undergoing scheduled abdominal surgery using SpotOn™ and compared these with those obtained using non-contact forehead infrared, infrared ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Importantly, the frequent use of these instruments in clinical settings generates a significant amount of waste production, particularly of disposable plastic cannulas (caps). However, the study in [38] presented a rather small sample size and the correlation was surprisingly good, especially for Non-Contact TMs on the forehead. In most cases, this is not possible because the influencing factors (especially sweating in febrile but also non-febrile subjects), especially with elevated body temperatures, are too robust and cause large deviations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Importantly, the frequent use of these instruments in clinical settings generates a significant amount of waste production, particularly of disposable plastic cannulas (caps). However, the study in [38] presented a rather small sample size and the correlation was surprisingly good, especially for Non-Contact TMs on the forehead. In most cases, this is not possible because the influencing factors (especially sweating in febrile but also non-febrile subjects), especially with elevated body temperatures, are too robust and cause large deviations.…”
Section: Discussionmentioning
confidence: 88%
“…Some authors have highlighted the poor performance of electronic axillary and tympanic thermometers compared to measurements of core body temperature [37]. Kameda [38] stated that a Tympanic Infrared TM can effectively approximate the core temperature and is quick and easy to use. Importantly, the frequent use of these instruments in clinical settings generates a significant amount of waste production, particularly of disposable plastic cannulas (caps).…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting results have been found in determining its accuracy to predict fever, particularly when non-standardized protocols are adopted (e.g., distance, position, etc.) and the devices are not properly calibrated [8,[50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Kameda, it was reported that temperature measured using a non-contact forehead infrared thermometer displayed a good correlation with the core temperature, and the correlation coefficient was higher than those for the temperatures measured using infrared tympanic and axillary thermometers [ 24 ]. The results revealed excellent accuracy comparable to tympanic temperature, with clinically sufficient precision.…”
Section: Discussionmentioning
confidence: 99%